The Effects of Destination Attributes and Benefits on Decision Making of MICE Stakeholders in Medan City - Nursiah Fitri; Jumjuma; Faulina (International ABEC, 2021)
Medan City is one of the government-appointed MICE-destination. Harsh and strict competition amongst tourist destinations demands support, participation, and investment from stakeholders. This study is focused more on the perceptions of stakeholders towards the destination attributes of Medan City and the benefit of MICE activities on decision making. The population used in this study is MICE stakeholders in Medan City, consisting of planners who have experience as EOs (Event Organizers), travel agencies, hotels, venues, and the government tourism office. Using the Lameshow formula, a sample of 96 people was determined. The sampling technique used in this study was the purposive sampling technique. PLS (Partial Least Square) structural equation modelling was used for the analysis. The results showed that destination attributes had a positive but not significant effect on decision making. Destination attributes have a positive and significant effect on benefits. Benefits have a positive and significant effect on decision-making. Destination attributes through benefits have a positive and significant effect on decision-making.